PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI, LOCUS OF CONTROL INTERNAL DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KINERJA KARYAWAN DI LEMBAGA PERKREDITAN DESA (LPD) KABUPATEN KARANGASEM - I Gede Dodi Saputra; Kadek Dewi Padnyawati (UNHI Press, 2022)
Performance is the result someone's work that shows the employee's achievements and is responsible for the tasks. This study to analysis the effect of the effectiveness of AIS, locus of control and top management support on the performance of LPD employees in Karangasem Regency. The form of research is associative using a questionnaire. The technique of determining the sample is purposive sampling, the sample is 90 people withmultiple regression analysis. The results of the analysis, namely the effectiveness of SIA, locus of control and top management support affect the performance of employees at the Karangasem Village Credit Institution